The effects of a social and talent development intervention for high ability youth with social skill difficulties. (2nd January 2017) - Foley-Nicpon, Megan; Assouline, Susan G.; Kivlighan, D. Martin; Fosenburg, Staci; Cederberg, Charles; Nanji, Michelle
Abstract: Contemporary models highlight the need to cultivate cognitive and psychosocial factors in developing domain-specific talent. This model was the basis for the current study where high ability youth with self-reported social difficulties ( n  = 28, 12 with a coexisting disability) participated in a social skills and talent development intervention over the course of a two-week summer enrichment program. Compared to high ability youth not in the social skills intervention ( n  = 9), participants reported positive changes in friendship qualities (help), indicating a treatment effect. Among all participants, positive changes were reported in friendship companionship and security, suggesting the talent development program alone had significant impact on psychosocial factors (friendship qualities). For those in the social skills group, higher scores on performance approach goal orientations were related to lower change scores in friendship closeness, suggesting if one is driven academically to outperform peers, this may negatively affect their ability to form close ties with peers.